Crystal Structures of Bacterial (6‐4) Photolyase Mutants with Impaired DNA Repair Activity1. (27th January 2017) - Zhang, Fan; Ma, Hongju; Bowatte, Kalinga; Kwiatkowski, Dennis; Mittmann, Esther; Qasem, Heba; Krauß, Norbert; Zeng, Xiaoli; Ren, Zhong; Scheerer, Patrick; Yang, Xiaojing; Lamparter, Tilman
Abstract: PhrB from Agrobacterium fabrum is the first prokaryotic photolyase which repairs (6‐4) UV DNA photoproducts. The protein harbors three cofactors: the enzymatically active FAD chromophore, a second chromophore, 6, 7‐dimethyl‐8‐ribityllumazine (DMRL) and a cubane‐type Fe‐S cluster. Tyr424 of PhrB is part of the DNA‐binding site and could provide an electron link to the Fe‐S cluster. The PhrBY 424F mutant showed reduced binding of lesion DNA and loss of DNA repair. The mutant PhrBI 51W is characterized by the loss of the DMRL chromophore, reduced photoreduction and reduced DNA repair capacity. We have determined the crystal structures of both mutants and found that both mutations only affect local protein environments, whereas the overall fold remained unchanged. The crystal structure of PhrBY 424F revealed a water network extending to His366, which are part of the lesion‐binding site. The crystal structure of PhrBI 51W shows how the bulky Trp leads to structural rearrangements in the DMRL chromophore pocket. Spectral characterizations of PhrBI 51W suggest that DMRL serves as an antenna chromophore for photoreduction and DNA repair in the wild type. The energy transfer from DMRL to FAD could represent a phylogenetically ancient process. Abstract : Agrobacterium PhrB is a prokaryotic (6‐4) photolyase with an FAD chromophore, a DMRL antenna chromophore and an Fe‐S cluster. Here, crystal structures of PhrB mutants were investigated. (A) Structural details of PhrBY424F and PhrBWT in the region of Tyr/Phe 424, close to the lesion‐binding site. PhrBY424F is characterized by reduced DNA repair activity. (B) Structural details of PhrBI51W and PhrBWT in the region of DMRL. The PhrBI51W mutant has lost DMRL due to steric repulsion. Tyr40 forms a hydrogen bond with DMRL in the wild‐type protein but moves away from the pocket in the mutant.